(untitled) (Journal of educational development exploration, 2025)
This paper focuses on the dilemma of rural community education development, takes integrated education as the theoretical framework, and analyzes the current problems of rural community education such as lack of resources, insufficient subject coordination and weak sustainability through empirical research. The study finds that it is necessary to build a community-led integrated education model from the three dimensions of subject aggregation (government, school, community organization, etc.), content expansion (basic + quality + development education), and form innovation (multiple linkage mechanism) to strengthen the social support network of community education and help rural revitalization and talent cultivation.